Scientific Approach to Learning Science in Elementary Schools - Siti Nur’ariyani; Jumyati Jumyati; Yuliyanti Yuliyanti; Lukman Nulhakim; Suroso Mukti Leksono (Jurnal Penelitian Pendidikan IPA, 2023)
Science learning elementary schools aims to maximize the concept of science in helping daily life processes that aim to increase students' positive attitudes in solving problems in the community environment. Through the literature research method, the researcher will carry out the process of collecting literature data that has relevance to the research topic chosen by the researcher. The collected data will undergo categorization and analysis by researchers. Before drawing conclusions, a comprehensive review of the relevant literature will be carried out. The scientific approach to learning is a pedagogical method that aims to equip students with the ability to identify or find problems through observation, asking questions, formulating hypotheses, collecting data using various techniques, analyzing data, drawing conclusions, and communicating findings, concepts, laws or principles. The scientific method has been developed to facilitate students' acquisition of knowledge and understanding of diverse subject matter. The scientific method allows the acquisition of information from a variety of sources, apart from one-way instructions from an educator. Utilization of the scientific method in the process of scientific learning is a scientific inquiry approach that is systematic and rigorous